Sum of all the interior angles = (5-2)x180 = 540°
540 - 100 - 120 - 100 - 90 = 130°
So the last unknown angle in the polygon is 130°
Sum of all the adjacent angles on a straight line is 180°
Angle 1 = 180 - 130 = 50°
The roots would be x=-5 and x=-4 but with that website you just do -5 and -4
If you're looking for a fraction:
Think of it this way, the 9 is in the 10th place. The 6 is in front of the decimal. So, it's 69/10. The 10 takes the place of the 9, the "/" is the decimal moved to the right one space.
Or
If you're looking for a mixed number:
You basically split the above fraction "69/10" up into two separate pieces. So, it's
6 9/10.
Answer:
-0.6309
Step-by-step explanation:
Using the change of base formula,
Log 1/2 to base 3 = Log1/2 ÷ Log 3 = Log 0.5 ÷ Log 3
Log 0.5 = -0.3010
Log3 = 0.4771
Log 0.5 ÷ Log 3 = -0.3010 ÷ 0.4771 = -0.6309
Answer:
The first thing you do is:
Step-by-step explanation:
How to calculate 60 divided by 19
Here we will show you step-by-step with detailed explanation how to calculate 60 divided by 19 using long division.
Before you continue, note that in the problem 60 divided by 19, the numbers are defined as follows:
60 = dividend
19 = divisor
Step 1:
Start by setting it up with the divisor 19 on the left side and the dividend 60 on the right side like this:
1 9 ⟌ 6 0
Step 2:
The divisor (19) goes into the first digit of the dividend (6), 0 time(s). Therefore, put 0 on top:
0
1 9 ⟌ 6 0
Step 3:
Multiply the divisor by the result in the previous step (19 x 0 = 0) and write that answer below the dividend.
0
1 9 ⟌ 6 0
0
Step 4:
Subtract the result in the previous step from the first digit of the dividend (6 - 0 = 6) and write the answer below.
0
1 9 ⟌ 6 0
- 0
6
Step 5:
Move down the 2nd digit of the dividend (0) like this:
0
1 9 ⟌ 6 0
- 0
6 0
Step 6:
The divisor (19) goes into the bottom number (60), 3 time(s). Therefore, put 3 on top:
0 3
1 9 ⟌ 6 0
- 0
6 0
Step 7:
Multiply the divisor by the result in the previous step (19 x 3 = 57) and write that answer at the bottom:
0 3
1 9 ⟌ 6 0
- 0
6 0
5 7
Step 8:
Subtract the result in the previous step from the number written above it. (60 - 57 = 3) and write the answer at the bottom.
0 3
1 9 ⟌ 6 0
- 0
6 0
- 5 7
3